Electrical Muscular Stimulation terhadap Penyembuhan Luka dan Kenyamanan Pasien Ulkus Kaki Diabetik (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of EMS on healing diabetic foot ulcers. The method used was a pre-post test design using a paired sample t-test conducted at the Andalas Health Center and Lubuk Buaya Health Center with as many as 22 respondents with a total sampling technique. The measuring tool used is the BWAT assessment sheet. The results showed an effect of EMS on wound healing with a p-value